Pseudomonas fluorescens biofilms subjected to phage phiIBB-PF7A - Sillankorva, Sanna (2008)
Background: Pseudomonas fluorescens is an important food spoilage organism, usually found in the form of biofilms. Bacterial biofilms are inherently resistant to a variety of antimicrobial agents, therefore alternative methods to biofilm control, such as bacteriophages (phages) have been suggested. Phage behavior on biofilms is still poorly investigated and needs further understanding. Here we describe the application of phage ϕIBB-PF7, a newly isolated phage, to control P. fluorescens biofilms. The biofilms were formed under static or dynamic conditions and with or without renewal of medium. Results: Conditions for biofilm formation influenced the feature of the biofilm and the morphology of P. fluorescens. Biomass removal due to phage activity varied between 63 and 91% depending on the biofilm age and the conditions under which the biofilm had been formed and phages applied. Removal of the biofilm by phage treatment was faster in younger biofilms, but the same number of surviving cells was detected in all tested biofilms, after only 4 h of treatment, even in older biofilms. Under static conditions, a 3 log higher number of phage progeny remained either inside the biofilm matrix or attached to the substratum surface than under dynamic conditions, pointing to the importance of experimental conditions for the efficacy of phage entrapment into the biofilm. Conclusion: Phage ϕIBB-PF7A is highly efficient in removing P. fluorescens biofilms within a short time interval. The conditions of biofilm formation and applied during phage infection are critical for the efficacy of the sanitation process. The integration of phages into the biofilm matrix and their entrapment to the surface may be further beneficial factors when phage treatment is considered alone or in addition to chemical biocides in industrial environments where P. fluorescens causes serious spoilage.